Effect of preservative treatment on physical and mechanical properties of bamboo (Gigantochloa scortechinii) strips - Baharuddin, Norhazaedawati; Seng, Hua Lee; Uyup, Mohd Khairun Anwar; Md Tahir, Paridah (North Carolina State University, 2022)
Using a vacuum pressure cylinder, Gigantochloa scortechinii was treated with boron and copper chrome boron (CCB) preservative at different concentrations of 2% and 3%. The treatability of untreated and treated bamboo, as well as its physical and mechanical properties, were investigated. Both preservatives showed a high level of penetration into the bamboo strips. Weight percent gain (WPG) and extent of retention of CCB-treated bamboo strips were higher than those of the boron-treated samples. Swelling and shrinkage were proportionately reduced with treatment, with a significant difference between radial and tangential dimensions. When compared to untreated bamboo, treated bamboo showed a greater reduction in radial swelling but a lower reduction in shrinkage. The mechanical properties of untreated and treated samples differed in modulus of elasticity (MOE) and compression. Untreated samples had the highest MOE of 26,100 N.mm-2, while boron and CCB had MOE values of 22,800 and 22,900 N.mm-2, respectively. Copper chrome boron samples had the highest compression value of 86.3 N.mm-2, while the boron and untreated samples had values of 84.0 and 78.3 N.mm-2, respectively.